EROSION HAZARD LEVEL PREDICTION IN LAKE OF SENTARUM AREA - Rizky, Firgenius; Soeryamassoeka, SB.; Kartini, Kartini (Fakultas Teknik Universitas Tanjungpura, 2024)
The Sentarum Lake region, a conservation area in Kalimantan, is integral to the Kapuas River Basin, which is recognized nationally. Ensuring its sustainability demands diverse studies, including erosion risk assessment. Accurate predictions are vital due to the region's ecosystem role in West Kalimantan. Estimating erosion magnitude provides crucial data on sedimentation, which impacts the sustainability of endemic flora and fauna. This study aims to (a) pinpoint erosion factors in Lake of Sentarum, (b) assess erosion hazard levels, (c) create an erosion hazard map with ArcGIS, and (d) prescribe soil conservation measures. Methods encompassed (a) field and institutional surveys for data gathering and (b) the USLE method for erosion hazard analysis. Identifying erosion factors in the Sentarum Lake area reveals rainfall, soil type, slope, and land cover as significant influencers. Analysis indicates heavy erosion hazards for Inceptisol and Utilosol soils, except in areas with primary dryland forest or flat-sloped dryland agriculture where hazards are heavy. Peat-containing soils are especially prone to erosion. Oxisol soils on flat slopes with agricultural land cover face heavy hazards, while moderate hazards occur in dryland agriculture on steeper slopes. The region faces considerable erosion risk, particularly in specific soil and land cover conditions, emphasizing the need for targeted soil conservation measures. Thus, the Sentarum Lake area is highly susceptible to erosion, necessitating specific soil conservation measures. Structural methods like constructing bench terraces prove more effective than non-structural ones, such as tillage and contour line planting, reducing erosion hazard by approximately 96%.